When influencers get real: how do customers react? - Andriasan Sudarso; Hendra Hendra; Wan Suryani (Journal of Innovation in Business and Economics, 2025)
The shifting digital marketing landscape highlights the central role of social media influencers, with a trend towards more authentic and vulnerable content emerging in response to increasing consumer skepticism. This research aims to investigate the direct influence of influencer vulnerability (measured through authenticity, relatability, and responsiveness), influencer trust, influencer credibility, and influencer viewing frequency on consumer purchase intention. Data was collected through an online survey of 147 active social media users who follow influencers. The results of multiple regression analysis show that influencer authenticity and relatability have a positive and significant influence on purchase intention. Similarly, influencer trust and credibility, as well as influencer viewing frequency, also positively influence purchase intention. Interestingly, influencer responsiveness and gender were not found to have a significant influence. These findings confirm that the power of authenticity and emotional connection, supported by trust and credibility, and consistent exposure, are key to driving purchase intention in an increasingly transparent influencer era. Managerial implications include the importance of influencers in building genuine and relevant connections, while brands should focus on long-term partnerships that leverage credibility and exposure frequency